PROTEIN BIOSYNTHESIS IN YEASTS CANDIDA RUGOSA BCB-925 UNDER HIGH TEMPERATURE (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The intensity of termoshock proteins biosynthesis in yeasts Candida rugosa BCB-925 was investigated. It has been shown that under high temperature (44°C) the synthesis of comparatively low-molecular proteins (M